Pengaruh Terapi Senam Otak terhadap Tekanan Darah, Status Fungsional, dan Fungsi Kognitif pada Lansia dengan Hipertensi: - Fratama, Ferry Fadli; Rizani, Khairir; Prayogi, Bisepta; Sofia, Norlaila (Jurnal Skala Kesehatan, 2025)
Hypertension in elderly is often accompanied by cognitive and functional decline affecting quality of life. Brain gym as a non-pharmacological intervention potentially addresses these issues through neuroplasticity stimulation. Objective this research to analyze the effects of brain gym on blood pressure, functional status, and cognitive function in elderly with hypertension. A quantitative quasi-experimental pretest-posttest one group design study involving 15 hypertensive elderly in Banjar Regency. Brain gym intervention was conducted for 3 times/week for 3 weeks, 30 minutes/session. Measurements used digital sphygmomanometer, Barthel Index, and MMSE. Data were analyzed using Paired t-test and Wilcoxon Signed Rank Test. Significant reduction in systolic blood pressure (162.93 to 148.33 mmHg, p=0.000) and diastolic blood pressure (100.60 to 90.87 mmHg, p=0.001) occurred. Functional status improved significantly (Z=-2.236; p=0.025) and cognitive function showed significant improvement (Z=-2.646; p=0.008) with 93.3% respondents achieving intact intellectual function. Brain gym effectively reduces blood pressure and improves functional and cognitive status in hypertensive elderly.